The Physical Role of Mesenchymal Cells Driven by the Actin Cytoskeleton Is Essential for the Orientation of Collagen Fibrils in Zebrafish Fins - Kuroda, Junpei; Itabashi, Takeshi; Iwane, Atsuko H.; Aramaki, Toshihiro; Kondo, Shigeru (Frontiers in Cell and Developmental Biology, 2020)
Fibrous collagen imparts physical strength and flexibility to tissues by forming huge complexes. The density and orientation of collagen fibers must be correctly specified for the optimal physical property of the collagen complex. However, little is known about its underlying cellular mechanisms. Actinotrichia are collagen fibers aligned at the fin-tip of bony fish and are easily visible under the microscope due to their thick, linear structure. We used the actinotrichia as a model system to investigate how cells manipulate collagen fibers. The 3D image obtained by focused ion beam scanning electron microscopy (FIB-SEM) showed that the pseudopodia of mesenchymal cells encircle the multiple actinotrichia. We then co-incubated the mesenchymal cells and actinotrichia in vitro, and time-lapse analysis revealed how cells use pseudopods to align collagen fiber orientation. This in vitro behavior is dependent on actin polymerization in mesenchymal cells. Inhibition of actin polymerization in mesenchymal cells results in mis-orientation of actinotrichia in the fin. These results reveal how mesenchymal cells are involved in fin formation and have important implications for the physical interaction between cells and collagen fibers.